Biochemical and Microbial Changes in Ice-stored Three Small Indigenous Fish of North-East (India) - Nath, Kapil Deb; Majumder, Ranendra Kumar (Indian Journal of Hill Farming, 2018)
The biochemical, microbial and organoleptic changes in three commercially important small indigenous fishes (Mystus gulio, Puntius sophore and Gudusia chapra) during ice storage has been studied. Proximate analysis revealed the moisture, ash, protein and lipid contents were 74.76%, 1.58%, 16.87% and 5.69%in M. gulio, 72.55%, 1.72%, 18.21% and 4.49%in P. sophore, and, 73.18%, 1.77%, 16.24% and 4.43% in G. chapra. Based on the biochemical, microbiological and organoleptic evaluation, the shelf-life of these fishes in ice-stored condition was considered to be 13 days, 10 days and 13 days respectively. The TVBN was increased to 29.87 mg% on 10th day of ice-storage in P. sophore, whereas, it crossed the border line of spoilage on 13th day in M. gulio and G. chapra. The aerobic plate count was reached to 6 log cfug-1 on 13th day in M. gulio and G. chapra and 10th day for P. sophore. Sensory analysis was well-correlated with the biochemical changes in fish. From this, it was concluded that, the edible quality of ice-preserved M. gulio and G. chapra remain upto 13 days and P. sophore upto 10 days.